Fractional Modeling of Driver’s Dynamics. Part 1: Passive Feedback and Steering Wheel Hand Link - Moreau, Xavier; Khemane, Firas; Malti, Rachid; Mermoz, Jean-Luc (Journal of Applied Nonlinear Dynamics, 2026)
This paper is the first part of a study related to modeling drivers dynamics in the overall driving loop in the context of disturbance rejection and trajectory tracking. The final objective is to dispose of a library of drivers models usable in a simulation context for Global Chassis Control (GCC) of automotive vehicles. Small angle variations are applied on the steering wheel and hence the use of a linear model is fully justified. The driver’s dynamics is first of all modeled by using a rational transfer function and then a fractional one. More specifically, the first part of the study presents the experimental set-up, named instrumented chair, and describes the experimental protocol. Then different models parts of the experimental set-up are established. Next, passive feedback and steering wheel/hand link is modeled. It is shown that a fractional model, as compared to a rational one, allows to enhance by a factor of 2.7 the criterion in modeling dissipative phenomena. The second part of the study treats both driver steering feel and visual feedback modeling, using a set-membership approach.